Better call Saul. Season four [videorecording (DVD)] - Spiro, Minkie; MacLaren, Michelle, 1965-; Odenkirk, Bob, 1962-; Odenkirk, Bob, 1962-; Banks, Jonathan, 1947-; Seehorn, Rhea, 1972- (Sony Pictures Home Entertainment, 2019)
Follows the trials of criminal lawyer Saul Goodman.